Sinais e sintomas preditivos do estado nutricional em pacientes com câncer de cabeça e pescoço de diferentes sítios primários antes do tratamento oncológico - Adriana Palhares de Carvalho (2018)
People diagnosed with head and neck cancer (HNC) represent a category of patients who may potentially develop nutritional problems due to mechanical obstruction of the tumor to the passage of food and the presence of signs and symptoms related to the disease itself and to the treatment. Malnutrition before treatment occurs in 30.0% to 80.0% of patients with HNC, in whom the main cause stems from insufficient food intake. In the pre- treatment period, signs and symptoms associated with HNC are frequently observed in this oncological population, but they present in an inhomogeneous way between the different subsites of the head and neck. The objectives of the study were: 1) To evaluate the influence of signs and symptoms on the nutritional status before the treatment in patients with HNC; 2) To describe the nutritional status in pre-treatment; 3) To evaluate the association of nutritional status with patient characteristics and cancer characteristics; 4) To check the association of signs and symptoms present with the location of the HNC. Based on these objectives, a retrospective cross-sectional study was performed at UFMG “Hospital das Clínicas” patients diagnosed with squamous cell carcinoma at the primary sites of the mouth, oropharynx, hypopharynx and larynx. The patients were evaluated in the pre- treatment period through data obtained from medical records and the nutrition sector. In addition to the general characteristics and cancer, were collected anthropometric information, nutritional diagnosis - evaluated through the Subjective Global Assessment -, and data on 10 predictive signs and symptoms of nutritional status – functional dysfunction, altered food intake, dysphagia, dysgeusia, hiporexia, odynophagia, trismus, xerostomia, nausea and vomit. The study involved 186 patients, mostly men (86.6%) and in advanced cancer staging (86.6%). Severe malnutrition was observed in 42.5% of the population and the main symptoms were altered food intake (69,9%), odynophagia (49,2%) and dysphagia (47,0%). The presence of at least one sign or symptom was a significant independent predictor of suspected malnutrition or moderate malnutrition (p = 0.004) and severe malnutrition (p = 0.019). It was observed that the greater the number of signs and symptoms, the greater the worsening of nutritional status. Eight of the 10 signs and symptoms evaluated showed a significant correlation with malnutrition: functional dysfunction, altered food intake, dysphagia, dysgeusia, hiporexia, odynophagia, trismus e xerostomia. Patients with tumors on the base of tongue, hypopharynx, oral tongue and supraglottic were the ones with the greatest amount of signs and symptoms. Advanced staging (p <0.001) and HNC subsites (p <0.001) - oral tongue, base of tongue and hypopharynx -, had higher frequencies of severe malnutrition. It is concluded that malnutrition is high in the pre-treatment period, and that the more advanced the cancer and the greater the number of symptoms present, the greater the prevalence of malnutrition. Patients with cancer in oral tongue, base of tongue, hypopharynx and supraglottic present a higher prevalence of malnutrition compared to other sites of head and neck cancer.